27‐Hydroxycholesterol promotes metastasis by SULT2A1‐dependent alteration in hepatocellular carcinoma. Issue 8 (13th June 2022) - He, Taochen; Tao, Baorui; Yi, Chenhe; Zhang, Chong; Zhang, Peng; Shao, Weiqing; Li, Yitong; Chen, Zhenmei; Lu, Lu; Jia, Huliang; Zhu, Wenwei; Lin, Jing; et al.
Abstract: Oxysterol metabolism plays an important role in the initiation and development of various tumors. However, little is known that the metabolic alternation can promote the metastasis of hepatocellular carcinoma (HCC). In this study, we identify the sulfotransferase family 2A member 1 (SULT2A1) to 27‐hydroxycholesterol (27‐OHC) metabolic axis as playing a critical role in HCC metastasis. The level of 27‐OHC closely corresponded with HCC metastasis instead of proliferation in vitro and in vivo. Also, the expression of SULT2A1 is extremely downregulated in human HCC tissues and is correlated with poor prognosis and tumor metastasis. Gain‐ and loss‐of‐function studies reveal that SULT2A1 suppresses the metastasis of HCC by regulating the level of 27‐OHC. Further mechanistic studies indicated that SULT2A1‐dependent alternation of 27‐OHC activates the nuclear factor‐κB signaling pathway and promotes HCC metastasis by enhancing Twist1 expression and epithelial–mesenchymal transition. In conclusion, our findings indicate the relationship between the metabolism of 27‐OHC and the metastasis of HCC. Moreover, SULT2A1 could act as a potential prognostic biomarker and a therapeutic target for preventing HCC metastasis. Abstract : In this study, we identify sulfotransferase family 2A member 1 (SULT2A1) to 27‐hydroxycholesterol (27‐OHC) metabolic axis as a critical role in HCC metastasis. Moreover, SULT2A1 may act as a potential prognostic biomarker and a therapeutic target for preventing HCC metastasis.